ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HASIL AUDIT INTERNAL (Studi Persepsi Aparat Intern Pemerintah Kota Surakarta dan Kabupaten Boyolali) - Annisa Parasayu; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
ABSTRACTThis research aim to analyze the influence of independency, objectivity, knowledge, job experience, integrity, and ethics audit of internal audit quality. The population of this research is the internal control of goverment officer on the Inspectorate of the city in Surakarta and Boyolali. The research data collection using questionnaire. Sampling using sensus method and number of samples of 51 respondents. The data analysis technique in this research using multiple regression analysis.The results showed that the objectivity, job experience, integrity, and ethics audit have a significant impact on internal audit quality, while the independency and knowledge do not have a significant impact on internal audit quality. Value of the coefficient of determination indicates the independency, objectivity, knowledge, job experience, integrity, and ethics audit that together affect to internal audit quality of 85% while the remaining 15% are influenced by other outside factor model.